Counterspace Game Elements for This Pansexual Pilipina American Player's Joy, Rest, and Healing: An Autoethnographic Case Study of Playing Stardew Valley - Cruz, Erica Principe (Gamevironments, 2022)
Single player digital games can be safe environments for players; e.g., Lost in a Good Game discusses Blake Stone (1993) as a safe place that satisfied intrinsic needs and offered respite from external troubles (Etchells 2019, 67). However, research on games like Grand Theft Auto III (2001) discusses them as environments that perpetuate stereotypes and justify white supremacy (Leonard 2003, 6). As a pansexual Pilipina American player, I turned to single player digital games as safe environments for my personal joy, rest, and healing. Too many times, they became unsafe places where I felt sad, angry, tired, and hurt. Counterplay, or player tactics for subverting game developers' original intentions, like resisting capitalism and colonialism in Minecraft (2011) (Huuhka 2019, 220), is one admirable form of recourse. Complementary to counterplay, I propose digital games can be counterspaces, or safe spaces (often at the periphery though they can be at the center of a dominant culture) for supporting marginalized individuals (Ong, Smith and Ko 2018, 206). I offer a preliminary set of counterspace game design principles by analyzing elements of Stardew Valley (2016) through an autoethnographic play lens. I synthesize key aspects that support this pansexual Pilipina American player's joy, rest, and healing. Specifically, I focus on single player game elements that enable joyful belonging of my intersectional identities, offer restful alternatives to othering realities, and provide healing narratives of hope and strength in the face of entrenched systems of oppression. While this work is centered on my own play of a single player game in relation to my lived experiences, it aims to spur more work around games that uplift marginalized individuals by centering their joy, rest, and healing.